EVALUATION OF THE KENYAN KADHI’S COURT BENCH BOOK FROM AN ISLAMIC SHARIA PERSPECTIVE: FOCUSING ON THE MARRIAGE SECTION - Abdulrahman, Manswab Mahsen; Walusimbi, Abdul Hafiz Musa (Jurnal Syariah, 2025)
This study critically evaluates the Kadhis Court Bench Book, specifically examining the marriage section in Chapter Four, Articles 1 through 20, via the framework of Islamic Sharia. It assesses the strengths and weaknesses of these provisions, focusing on aspects of clarity, consistency, and adherence to Islamic legal principles. The research problem regarding the enactment of the Kadhis Court Bench Book arises from the judiciary's acknowledgment of inconsistencies in verdicts resulting from divergent opinions among the various schools of thought. To conduct this evaluation, a qualitative approach will be adopted, using methods such as document analysis, comparative analysis, case study review, and data interpretation. The findings show that the Bench Book lacks systematic organization, with certain sections deviating from essential Sharia principles or offering insufficient clarity. The reliance on lesser-known madhhabs in its application in Kenya contributes to inconsistencies, as certain provisions do not fully adhere to fundamental Sharia principles. Some provisions are difficult to implement and the arisal of ambiguities and gaps in specific provisions can lead to differing interpretations. Ultimately, the study recommends the creation of a systematical framework for continuous monitoring and evaluation of the Bench Book’s implementation, facilitating timely revisions to address emerging challenges in marital jurisprudence.